Hot pressed pellets of thallium doped bismuth telluride alloys for thermoelectrics. Issue 184 (13th October 2017) - Gupta, Raj K.; Puri, Nidhi; Mehra, N. C.; Mahapatro, Ajit K.; Tandon, Ram P.
ABSTRACT: Thallium doped bismuth telluride alloys (Bi2-x Tlx Te3 ) are synthesized using solvothermal method, and pellets are formed using hot-press machine by applying 60 MPa pressure at 553 K temperature for 5 min. The X-ray powder diffraction for the as-synthesized Bi2-x Tlx Te3 alloys indicates phase purity and crystallographic structures. Scanning electron microscopy indicates highly compact plate-like structures for hot-pressed pellets. The energy dispersive X-ray spectrophotometer predicts a stoichiometric ratio of 2:3 for Bi and Te in the Bi2 Te3 . The newly prepared Bi2-x Tlx Te3 pellets could be utilized as an efficient material in thermoelectric devices for power generation from waste heat.